Experimental Analysis of Ventilated Brake Disc with Different Blade Configuration - Mahmod, Muhamad Ibrahim; Munisamy, Kannan M. (2006)
Most modern cars on the road using brake disc as the braking system to slow down and stop the car. Because of the better breaking performance, simpler design and easy to service, car manufacturer prefer disc brake rather than drum brake. During braking, the kinetic energy of a car is dissipated through frictional energy and greatly as heat energy. The excessive heat needs to be cooled faster otherwise the braking performance of the car will decrease. The heat removal has a close correlation with mass flow through the ventilated brake disc. From literature, there is no stationary test rig ever developed to study the mass flow through the ventilated brake disc. There is a lot on wheel testing, yet with other influence like rims, suspension system, coil spring and others. Thus an experimental rig to study the mass flow and differential pressure was developed in Department of Mechanical Engineering, University Tenaga Nasional. The experimental rig is design to cater for any configuration of ventilated brake disc blade design. This paper will present the effect of mass flow and differential pressure for a few blade design configurations.